2008
DOI: 10.1038/onc.2008.134
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel AML1-ETO fusion transcripts in pediatric t(8;21) acute myeloid leukemia: a report from the Children's Oncology Group

Abstract: t(8;21)(q22;q22) results in the AML1-ETO (A1E) fusion gene and is a common cytogenetic abnormality in acute myeloid leukemia (AML). Although insertions at the breakpoint region of the A1E fusion transcripts have been reported, additional structural alterations are largely uncharacterized. By RT-PCR amplifications and DNA sequencing, numerous in-frame and out-of-frame AML1b-ETO and AML1c-ETO transcripts were identified in 13 pediatric t(8;21) AMLs, likely resulting from alternate splicing, internal deletions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Here, we report for the first time that the plus/minus exon 9a ratio in FTs is significantly higher than in native transcripts ( P < 0.001). Given the fact that several splice variants have been reported to be present in RUNX1‐RUNX1T1 patient cells (14) one might speculate whether this extends to other RUNX1‐RUNX1T1 FT splice variants. However, while our data demonstrate that an altered balance in alternative splicing is operative in most RUNX1‐RUNX1T1 + patients, one of the patients with normal diagnosis splice variant ratio had persistently normal ratio both during therapy and at relapse (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report for the first time that the plus/minus exon 9a ratio in FTs is significantly higher than in native transcripts ( P < 0.001). Given the fact that several splice variants have been reported to be present in RUNX1‐RUNX1T1 patient cells (14) one might speculate whether this extends to other RUNX1‐RUNX1T1 FT splice variants. However, while our data demonstrate that an altered balance in alternative splicing is operative in most RUNX1‐RUNX1T1 + patients, one of the patients with normal diagnosis splice variant ratio had persistently normal ratio both during therapy and at relapse (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated a wide range of variant protein‐coding and noncoding transcripts generated from the RUNX1‐RUNX1T1 gene related to the utilization of different RUNX1 promoters and alternative RUNX1T1 exons (Era et al, ; Erickson et al, ; Kozu, Fukuyama, Yamami, Akagi, & Kaneko, ; Kozu et al, ; LaFiura et al, ; Mannari, Gascoyne, Dunne, Chaplin, & Young, ; M. Yan et al, ). The breakpoints in the RUNX1 gene cluster in intron 5 and the breakpoints in RUNX1T1 cluster in intron 1.…”
Section: Oncogenic Fusion Transcripts—partners In Cancermentioning
confidence: 99%
“…Several in-frame variants of these forms have been identified, and their final effects on the expression of AML1 responsive genes seem to vary from repressive to activating [65]. …”
Section: Molecular Genetics Of T(8;21)mentioning
confidence: 99%